THE EFFECT OF CREATINE USAGE ON YOUNG SOCCER PLAYERS’ BODY COMPOSITION AND AGILITY - Ates, Osman; Kirandi, Ozlem (Acta Scientiae et Intellectus, 2024)
This study was conducted with the aim of evaluating the effect of creatine usage on young athletes’ body composition and agility. 20 male soccer players with average age of 16,30±,73 participated in the study. Before starting the tests, the body weights and body compositions of the soccer players were tested with the TANITA BC-418 device. Among the obtained data, body mass index (BMI), body fat ratio, fat weight, lean body weight and total body fluid amount are available. Then, with the Illinois test, agility measurements were tested twice, right and left, according to the participant’s priority preference at each time. Between the two tests a participant was expected to reach the number of resting heart beats. Participants continued their training using 0.3 g of creatine monohydrate per kg for 5 days, taking 0.3 g of dry milk per kg for 5 days, without taking any food supplements. Body composition and Illinois agility test times were examined after participants’ dry milk and creatine loading. Although there was an increase in body weight, body fat percentage and total body fluid after creatine loading, no statistical significance was found (p> 0.05). Significant differences were found statistically between the first measurement (20,99) and the measurements made after creatine loading (21,77) in body mass index matching (p <0.05). Especially with the effect of tests done after creatine loading, positive significant differences were found between Illinois test times (p<0.05).